Organic optoelectronic interfaces with anomalous transient photocurrent. Issue 20 (28th May 2015) - Hu, Laigui; Liu, Xian; Dalgleish, Simon; Matsushita, Michio M.; Yoshikawa, Hirofumi; Awaga, Kunio
<x xml:space="preserve">Abstract</x> In this review, anomalous transient photocurrent from organic semiconductor devices in response to square-wave light pulses in the literature are discussed; current efforts to utilize these transients are highlighted, such as in transient-type photodetectors and artificial retinas.